A nonlinear adaptive sliding mode control strategy for modular high-temperature gas-cooled reactors. (May 2019) - Wang, Guoxu; Wu, Jie; Zeng, Bifan; Xu, Zhibin; Ma, Xiaoqian
Abstract: Modular high-temperature gas-cooled nuclear reactor (MHTGR) has attracted comprehensive attention for its reliable inherent safety, and an effective control strategy is needed to control the output power of the MHTGRs at desired levels. This paper aims to develop a nonlinear power-level tracking controller based on sliding mode control (SMC) strategy for the MHTGRs. By introducing Takagi-Sugeno (TS) fuzzy system for nonlinear modeling, the MHTGR model is represented by TS models. The control law is designed based on the TS models and the sliding mode surface that is defined as the tracking error, and an adaptive algorithm is also included in the proposed control law to reduce the chattering phenomenon of SMC. In addition, the stability of the closed-loop control system is also guaranteed by the proposed control law. To evaluate the performance of the proposed nonlinear adaptive sliding mode control (NASMC) strategy, a traditional nonlinear sliding mode control (TNSMC) strategy and a Proportional-Integral-Derivative (PID) control strategy are presented for comparison. Simulation results show the effectiveness and the advantages of the proposed NASMC strategy, and most importantly, the proposed NASMC strategy does not suffer from chattering.